Tolle superbiam: divitiae non nocebunt Community, Renunciation, and the Fall of Rome: Wealth in the Pelagian Controversy - Charlie Evans (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2025)
During the fourth and fifth centuries, discourse about Christian almsgiving and wealth proliferated widely as charitable institutions and ascetic communities began to form, such that “social norms and expectations regarding poverty were also in flux.”[i] Congregations across the Roman Empire were trying to discern what was the Christian way to understand the relationship between wealth and the Christian life: Should good Christians have wealth? Augustine’s and Pelagius’ early fifth-century discourses on wealth which the Pelagian Controversy produced were pivotal in providing answers to this question. Augustine’s views on wealth formally triumphed at Ravenna in 418. Good Christians could have wealth, so long as it was used appropriately rather than abused. The salience of Augustine’s affirmation of the potential of wealth to help in an individual’s salvation and serve the community’s good in the context of the cultural upheaval following the sack of Rome was indispensable in Augustine’s views on wealth becoming the orthodox view on wealth in the West. This paper will consider cultural moment surrounding the controversy, the Pelagian text De Divitiis, a host of Augustine’s writings on wealth, and secondary criticism of these respective writings in the course of the argument of this claim.